2006
DOI: 10.1021/ja063223j
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dynamic Behaviors of Water Molecules in Hydrated Pores

Abstract: Water molecules confined inside narrow pores are of great importance in understanding the structure, stability, and function of water channels. Here we report that besides the H-bonding water that structures the pore, the permanent presence of a significant, fast-moving fraction of incompletely H-bonded water molecules inside the pore should control the free entry and exit of water. This is achieved by means of complementary DSC and solid-state NMR studies. We also present compelling evidence from X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 26 publications
3
75
0
Order By: Relevance
“…10 Variable temperature powder X-ray diffraction and thermogravimetry 12 confirmed that water can be partially removed from the solids without destroying the crystal structures. These results prompted us to wonder about the mechanism of the diffusion of water in organic crystals which is a prerequisite of the gasÀsolid state deuteration process.…”
Section: ' Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…10 Variable temperature powder X-ray diffraction and thermogravimetry 12 confirmed that water can be partially removed from the solids without destroying the crystal structures. These results prompted us to wonder about the mechanism of the diffusion of water in organic crystals which is a prerequisite of the gasÀsolid state deuteration process.…”
Section: ' Introductionmentioning
confidence: 92%
“…10 We were intrigued by The Journal of Physical Chemistry C ARTICLE this finding and thought that knowledge of the individual rates could provide additional information about the mechanism of the gas/solid state deuteration and the diffusion of water through crystals. We thought that the method of choice to solve this problem would be attenuated total reflection infrared (ATR-IR) spectroscopy of the pure polycrystalline powders which would allow us to follow the different OH-stretching bands as a function of the time of exposure to heavy water vapor.…”
Section: ' Introductionmentioning
confidence: 99%
“…Various mobility of the water clusters incorporated within the pores and H-bonding waters that structure these pores was demonstrated in Refs. [251,307]. Liu et al demonstrated that anhydrous uric acid and its' dihydrate exhibited various mechanical properties of their single crystals despite the similarity of layered motifs formed by the acid [276].…”
Section: Analysis Of Solvent Associatesmentioning
confidence: 99%
“…Additionally, a core-sheath 1D ice structure has been detected in a neutron scattering experiment (5) where the core is a single-file water chain and the sheath is an octagon ice nanotube (provisionally named as 1D ice IVa). Previous classical molecular dynamics simulations (13,14) have suggested that the pentagon and heptagon ice nanotubes are 1D ice with mixed ferroelectric/antiferroelectric domains.Besides the carbon nanotubes, a large number of organic and inorganic species have been successfully synthesized as hosts for confining water on the nanoscale (4,17,(25)(26)(27)(28). Nevertheless, species that can lead to single-phase ferroelectric ice have not been demonstrated experimentally.…”
mentioning
confidence: 99%
“…Besides the carbon nanotubes, a large number of organic and inorganic species have been successfully synthesized as hosts for confining water on the nanoscale (4,17,(25)(26)(27)(28). Nevertheless, species that can lead to single-phase ferroelectric ice have not been demonstrated experimentally.…”
mentioning
confidence: 99%